CARA HALAL MEMILIKI HARTA - Tjek Tanti (TAQNIN: Jurnal Syariah dan Hukum, 2019)
Humans need wealth in meeting their needs. Property is a basic human need, both for clothing, food and shelter. With wealth someone supports himself, his family and also his religion. Therefore humans always look for it and try to get it. Treasure can provide happiness in this world and the hereafter if it is obtained from halal sources and used in the right things. But on the contrary property will be disastrous if obtained in the wrong way and used for bad things. Therefore, in obtaining the wealth of Muslims it is necessary to know the principles and norms in Islamic Law about how to obtain halal property. The following article discusses various matters relating to the halal way of owning assets.